Lipid Droplet-Related PLIN2 in CD68+ Tumor-Associated Macrophage of Oral Squamous Cell Carcinoma: Implications for Cancer Prognosis and Immunotherapy - He, Yijia; Dong, Yuexin; Zhang, Xinwen; Ding, Zhuang; Song, Yuxian; Huang, Xiaofeng; Chen, Sheng; Wang, Zhiyong; Ni, Yanhong; Ding, Liang (Frontiers in Oncology, 2022)
Background: PLIN2 (adipose differentiation-related protein) belongs to the perilipin family and is a marker of lipid droplets (LDs). Numerous types of tumor exhibit high PLIN2 level but its tumorigenic or tumor suppressive role has been in debate. Recently, LDs serve as innate immune hubs and showed antimicrobial capacity. We here aimed to investigate the heterogeneous functions of PLIN2 in tumor microenvironment and immune regulation. Methods: This retrospective study included 96 oral squamous cell carcinoma (OSCC) samples and analyzed the spatial distribution of PLIN2 by immunohistochemistry (IHC) and LDs level by oil red O staining. A total of 21 serial sections were obtained to analyze the relationship between PLIN2 and immune cells by IHC and Immunofluorescence(IF). Single cell sequencing was used to analyze cell locations of PLIN2. The values of diagnosis and prognosis of PLIN2 were also evaluated. Tumor Immune Estimation Resource (TIMER), cBioPortal databases and IHC analysis were used to investigate the relationship between PLIN2 and OSCC immune microenvironment. Results: PLIN2 was mainly expressed in tumor-infiltrating immunocytes (TIIs) of OSCC. Patients with high PLIN2 harbored more cytoplastic LDs. CD68+ tumor-associated macrophages (TAMs), instead of T cells and B cells, were found to be the main resource of PLIN2 in OSCC stroma and lung, pancreas, prostate, and testis. However, CD56+ NK cells also showed less extent of PLIN2 staining in OSCC. Moreover, patients with high PLIN2 level in immune cells had higher TNM stage, and were susceptible to postoperative metastasis, but escalated PLIN2 level in invasive tumor front independently predicted shorter metastasis-free survival. Furthermore, high PLIN2 presentation in microenvironment induced immune suppression which featured as less infiltration of CD8+ T cells and more CD68+ TAMs and Foxp3+ Tregs, and accompanied with more immune checkpoint molecules such as CSF1R, LGALS9, IL-10, CTLA-4 and TIGIT etc. Conclusion: CD68+ TAM-derived PLIN2 might participate in regulating immune balance of OSCC patients, which provides new insight into immune checkpoint therapy.